Utjecaj emisije CO2 iz motornih vozila na okolinu - Zavada, Josip (Promet - Traffic&Transportation, 2012)
This paper deals with the emissions of carbon dioxide from motor vehicles as an important exhaust gas in the process of building up the greenhouse effect. The discussion covers al/levels of energy con versions -from the primary energy sources to the completion of useful transport by motor vehicles. In this different primary forms of energy are taken into account: appropriate conversion methods for obtaining the motor fuels, different types of fuels, and different structures of engines in the vehicles. The corresponding emissions of carbon monoxide is translated into the unit of transport output i.e. the coefficient is determined of the emission of carbon dioxide as a relevant indicator of the influence of individual elements in the entire chain of con versions in the emission of carbon dioxide.